SELF-CONTROL MEDIATION: THE INFLUENCE OF ISLAMIC LEARNING AND PARENT’S SUPPORT ON STUDENT’S RELIGIOUS CHARACTER - Faidah, Ni'matul; Ratnawati, Siti Rohmaturrosyidah; Daryono, Rihab Wit (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
This research aimed to determine the influence of Islamic learning and parent’s support on religious character and the role of self-control in mediating the relationship between these two variables. The research method used was a quantitative approach with a survey method, involving 126 MTs Al-Istiqomah Dungus students as participants. The data collection technique used a Likert scale. Data analysis was carried out using PLS-SEM. The results of the analysis showed that Islamic learning β-value = 0.211 and ρ-value = 0.029 had a positive and significant influence on improving students’ religious character, while parent’s support β-value = 0.011 and ρ-value = 0.913 has a positive and insignificant influence. Self-control as a mediator of the relationship between Islamic learning and religious character obtained β-value = 0.158 and ρ-value = 0.000 which shows that self-control has partial mediation. Meanwhile, self-control in the relationship between parent’s support and religious character obtained β-value = 0.184 and ρ-value = 0.000 which shows that self-control has a full mediation. The implications of this research finding highlight the importance of self-control in the development of children's religious character. The suggestions given include improving the learning system by compiling an Islamic curriculum that can actualize religious values so that students can identify good and bad actions as a form of self-control. Parents needed to communicate intensively with their children to create comfort and confidence in carrying out correct actions as a manifestation of their ability to control themselves from disgraceful behavior.